Kajian Indeks Resiko Bencana dengan Kesiapan Puskesmas dalam Managemen Bencana Kesehatan di Kota Jambi - Andi Subandi; Dwi Noerjoedianto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to see the service system during a health disaster in the city of Jambi, namely Tahtul Yaman Puskesmas, Tanjung Pinang Health Center, and Aurduri Health Center. The short-term target is to find organizational standards and the role of the puskesmas team in disasters. The research method used survey analytics to assess the roles and functions that were involved in the health disaster management system and to analyze the readiness of 3 health centers in the city of Jambi. From the results of this study, according to the application of the Minister of Health Regulation number 75 of 2019 at the Tahtul Yaman Puskesmas, the Tanjung Pinang Health Center, and the first Aurduri Health Center, it is obtained from (1) There is no clear program regarding disaster management in each cluster at the Puskesmas, ( 2) Rapid Health Assessment (RHA) has not been implemented in the event of a disaster, (3) The coordination flow for the Puskesmas already exists, namely through referrals to the Abdul Manap Regional General Hospital, Jambi City and the Jambi City Health Office.